Evaluasi kinerja blower pada mesin pengering padi kapasitas 25-30 ton pada CV. XYZ: Evaluasi kinerja blower pada mesin pengering padi kapasitas 25-30 ton pada CV. XYZ - Anjani, Ratna Dewi; Yasin, Muhammad Nur; Musthafa, Luthfi; Gumelar, Reza (Universitas Muhammadiyah Metro, 2023)
The Abstract Rice is the staple food for more than 95% of the Indonesian people, but sometimes it is difficult for tired to fulfill this demand because in the processing of rice itself it is necessary to dry the grain first, but this cannot be done if the weather is not supportive and also drying rice which requires a large area of ​​land for cultivation. Doing drying is what usually becomes an obstacle for farmers if the drying process of rice grain is constrained it will disrupt the level of stability of rice productivity and the supply of rice to the community will be hampered which leads to disruption of national food security. In this rice drying machine there are several main components, namely a blower and also a heating furnace. A rice dryer machine is a machine that functions to dry rice where the system works using a blower and also a heater to distribute hot air which ultimately dries the rice in the drying process, the rice is placed in a tub. shelter where the bottom is given a cavity to channel the hot air fired by the blower currently developing there are various types. There are those who continue to use sunlight as an energy source through solar panels, there are also those who use a microcontroller system. The purpose of this research is to evaluate the blowers that have been designed to still rely on the electricity supply from PLN to operate, there are also those who use diesel engines by utilizing fuel to know the performance that generated by the blower then tested on the blower the test results show the blower component can work well and the evaluation results get a blower efficiency result of 98.12% this great efficiency is influenced by the amount of energy or driving power given to the blower